Genome‐wide variation within and between wild and domestic yak. (10th February 2014) - Wang, Kun; Hu, Quanjun; Ma, Hui; Wang, Lizhong; Yang, Yongzhi; Luo, Wenchun; Qiu, Qiang
Abstract The yak is one of the few animals that can thrive in the harsh environment of the Qinghai‐Tibetan Plateau and adjacent Alpine regions. Yak provides essential resources allowing Tibetans to live at high altitudes. However, genetic variation within and between wild and domestic yak remain unknown. Here, we present a genome‐wide study of the genetic variation within and between wild and domestic yak. Using next‐generation sequencing technology, we resequenced three wild and three domestic yak with a mean of fivefold coverage using our published domestic yak genome as a reference. We identified a total of 8.38 million SNPs (7.14 million novel), 383 241 InDels and 126 352 structural variants between the six yak. We observed higher linkage disequilibrium in domestic yak than in wild yak and a modest but distinct genetic divergence between these two groups. We further identified more than a thousand of potential selected regions (PSRs) for the three domestic yak by scanning the whole genome. These genomic resources can be further used to study genetic diversity and select superior breeds of yak and other bovid species.